The Influence of Teacher Competence on Students' Critical Thinking Skills (A Survey at SMK Daarul Uluum, South Jakarta) - Rosidah, Rosidah; Kunaenih, Kunaenih (Jurnal Indonesia Sosial Sains, 2025)
The role of teacher competence in the education system is a major pillar in character formation, knowledge enhancement, and the development of a competent young generation. Amid the dynamic changes in the world of education, the role of teachers holds a very crucial position in guiding students to achieve good academic performance and shape good character as well. One of the primary roles of teachers is developing pedagogical competence to improve learning discipline. This study was motivated by the observation that students’ critical thinking skills are influenced by teachers’ pedagogical competence in classroom teaching, aiming to measure the extent of teacher competence’s influence on the critical thinking skills of students at SMK Daarul Uluum, Karet Kuningan, South Jakarta. The sample consisted of 30 students, and the study employed a descriptive analytical correlational method. By analyzing the data using the product moment correlation, the results show that the product moment coefficient (r_xy or r_o) is 0.225. This indicates that r_o is lower than r_t at a significant level of 5% (0.367) and at a significant level of 1% (0.470). Thus, since r_o < r_t at both significance levels, the null hypothesis is accepted, while the alternative hypothesis is rejected, meaning that there is a low influence of teacher competence on the critical thinking skills of students at SMK Daarul Uluum, South Jakarta.